Microsoft Sharepoint 2007 für Dummies - Williams, Vanessa L. (Wiley-VCH-Verl., 2007)
Annotation
Print version record
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Intranets; Serveurs Web; intranets